Intraoperative validation of quantitative T2 mapping in patients with articular cartilage lesions of the knee - Söllner, Stefan; Goldmann, A.; Muelheims, D.; Welsch, G. H.; Pachowsky, Milena (Osteoarthritis and Cartilage, 2017)
OBJECTIVE: The aim of this study was to compare T2 relaxation times of knee cartilage with intraoperative results for the assessment of early osteoarthritis (OA) and to define T2 values for the differentiation between healthy and degenerated cartilage. DESIGN: Twenty-one patients with cartilage lesions or moderate OA were examined using 3T magnetic resonance imaging (MRI). In this prospective study, a total of 882 regions of interest (ROIs) were examined by a sagittal, multi-echo, spin-echo T2 sequence and a morphological high-resolution three-dimensional, fat-saturated proton-density space sequence. Cartilage lesions were identified arthroscopically, graded by the International Cartilage Repair Society (ICRS) score in 42 defined ROIs per patient and consecutively compared with mean T2 values using analysis of variance and Spearman's rank correlation test. Receiver operating characteristics (ROC) curves were developed to identify threshold T2 values to differentiate between the ICRS grades. RESULTS: A total of 882 ROIs were examined and graduated in ICRS score 0 (67.3%), 1 (25.2%), 2 (6.2%) and the merged ICRS 3 and 4 (1.0%). T2 values increased with increasing grade of cartilage damage with a statistically significant positive correlation between T2 values and ICRS scores. A T2 value threshold of 47.6 ms was identified to differentiate between ICRS score 0 (normal) and all other grades (ROC curve analysis). CONCLUSION: T2 mapping might provide a diagnostic tool for the detection of early knee-joint cartilage damage and for the non-invasive differentiation between ICRS grades by MRI in clinical practice.
EVALuna2:212496